Reachability Does Not Explain the Middle Preference: A Comment on Bar-Hillel (2015). (23rd March 2016) - Rodway, Paul; Schepman, Astrid; Thoma, Volker
Choosing an object from an array of similar objects is a task that people complete frequently throughout their lives (e.g., choosing a can of soup from many cans of soup). Research has also demonstrated that items in the middle of an array or scene are looked at more often and are more likely to be chosen. This middle preference is surprisingly robust and widespread, having been found in a wide range of perceptual-motor tasks. In a recent review of the literature, Bar-Hillel (2015) proposes, among other things, that the middle preference is largely explained by the middle item being easier to reach, either physically or mentally. We specifically evaluate Bar-Hillel's reachability explanation for choice in non-interactive situations in light of evidence showing an effect of item valence on such choices. This leads us to conclude that the center-stage heuristic account is a more plausible explanation of the middle preference.